Water governance: assumptions to assign a new meaning to it - Mazzarino, Jane Márcia; Turatti, Luciana (Ciência e Natura, 2018)
Taking into consideration the current scenario of access to water resources and their significance for human survival, as well as the fact they have become a human right, it can be said that public policies of governance in this aspect need to go beyond their traditional format to effectively encompass participatory processes. Environmental public policies have shown not to satisfactorily respond to the challenges posed, which is partly due to the governance models employed. Studies on governance processes in the Brazilian context have indicated that, despite the alleged inclusiveness in the public policies processes, these transformative ideals have not been attained yet. This study aims at establishing theoretical assumptions on the concept of governance, so as to find elements to assign a new meaning to it, once it has been overused, with a subsequent loss of its signification, in order to contribute to studies on water governance in the scope of hydrographic basins. The method used is qualitative and bibliographic.